Pesticide chemistry and bioscience : the food-environment challenge - Brooks, G. T. (Gerald T.); Roberts, Terry R. (The Royal Society of Chemistry, 1999)
This volume, with contributions from leading international experts, reports on the need to produce high quality food whilst satisfying environmental concerns. Including material on natural products, modes of action and metabolism, it covers all the key areas in pesticide chemistry and related activities. The contents outline the developments that have taken place in approaches to crop protection and our ability to develop complex, environmentally acceptable strategies for weed, pest and disease control.